2003
DOI: 10.1016/s0262-8856(02)00126-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-band modelling of appearance

Abstract: Earlier work has demonstrated generative models capable of synthesising near photo-realistic grey-scale images of objects. These models have been augmented with colour information, and recently with edge information. This paper extends the Active Appearance Model framework by modelling the appearance of both derived feature bands and an intensity band. As a special case of featureband augmented appearance modelling we propose a dedicated representation with applications to face segmentation. The representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…Similar features are employed in [21] to create a robust similarity optimization criterion. In [27], the intensities appearance model is replaced by a mixture of grayscale intensities, hue channel and edge magnitude.…”
mentioning
confidence: 99%
“…Similar features are employed in [21] to create a robust similarity optimization criterion. In [27], the intensities appearance model is replaced by a mixture of grayscale intensities, hue channel and edge magnitude.…”
mentioning
confidence: 99%
“…We use homemade ZigBee-USB dongle, which embed a XBee module from Digi [10]. Whereas the wireless communication is not necessary in the standalone version, it still allows the system to be isolated from the main power line and thus, to be electrically safe for the user (the sensors are battery powered).…”
Section: Affective Computing and Video Gamesmentioning
confidence: 99%
“…al [5] found that a non-linear representation of edge structure could improve subspace matching. Stegmann and Larsen [24] report that building subspaces for AM in an augmented space of intensity, hue and edges performed better in the task of localizing faces. In similar fashion, [7] make use of wedgelet regression trees to reduce the computational complexity of standard Active AM.…”
Section: Representation In Subspace Analysismentioning
confidence: 99%